Perancangan Antarmuka Aplikasi Konversi Bilangan dan Warna Berbasis Android - Yesi Sriyeni; Maria Veronica (Jurnal Informatika Global)
ABSTRACTLearning activities do not always have to be done in the form of face-to-face lecture meetings. Learning can be done anywhere as long as it is supported by appropriate tools such as multimedia. The use of appropriate and interesting learning multimedia is felt necessary to increase student interest and learning achievement. Just like the material conversion of numbers and colors that have been considered as material that is quite difficult to be absorbed directly by students. Therefore, it is deemed necessary to design a media that can help lecturers convey material conversion of numbers and colors lighter and the material will be more easily understood by students. The multimedia interface design of learning numbers and color conversions is designed to be developed on the Android platform with a user centered design (UCD) approach. Interface testing is still carried out by researchers and only a few user samples. This is done in order to get feedback from a sample of users regarding the interface design that has been made so that it is right on target. There are several pages consisting of a splash page, a menu page, an introductory page, a study material page, a number calculator page, a color calculator page, a practice page, and a quiz page. Specifically for the quiz page, all quiz questions are planned to be timed. It aims to measure the success of absorption of numbers and color conversion material in the teaching and learning process carried out by students and lecturers. Keywords : android, multimedia, interface, calculatorABSTRAKKegiatan pembelajaran tidaklah harus selalu dilakukan dalam bentuk pertemuan kuliah langsung bertatap muka. Belajar bisa dilakukan dimana pun asalkan didukung dengan tools yang tepat seperti multimedia. Penggunaan multimedia pembelajaran yang tepat dan menarik dirasa perlu untuk meningkatkan minat dan prestasi belajar mahasiswa. Sama halnya seperti materi konversi bilangan dan warna yang selama ini dianggap sebagai materi yang cukup susah untuk diserap langsung oleh mahasiswa. Oleh karena itu dirasa perlu merancang sebuah media yang dapat membantu dosen menyampaikan materi konversi bilangan dan warna dengan lebih ringan dan materi pun akan lebih mudah dipahami oleh mahasiswa. Desain antarmuka multimedia pembelajaran konversi bilangan dan warna ini dirancang untuk dikembangkan pada platform android dengan pendekatan user centered design (UCD). Pengujian antarmuka masih dilakukan oleh peneliti dan beberapa sampel pengguna saja. Hal ini dilakukan guna mendapatkan umpan balik dari sampel pengguna mengenai desain antarmuka yang sudah dibuat sehingga tepat sasaran. Terdapat beberapa halaman yang terdiri dari halaman awal (splash page), halaman menu, halaman pendahuluan, halaman materi belajar, halaman kalkulator bilangan, halaman kalkulator warna, halaman latihan, dan halaman kuis. Khusus untuk halaman kuis, pengerjaan semua soal kuis direncanakan untuk diberi batas waktu. Hal ini bertujuan untuk mengukur keberhasilan penyerapan materi konversi bilangan dan warna dalam proses belajar mengajar yang dilakukan oleh mahasiswa dan dosen.Kata kunci : android, multimedia, antarmuka, kalkulator